(untitled) (Confluenţe Bibliologice, 2025)
In the period of 10 to 15 March 2014, at the Library of Kaunas University of Medical Sciences, Lithuania, was launched the project Tempus Information Services for Quality Improvement Study, MISISQ. The European coordinator is Kretaviciene Meile. Seven universities libraries participate in this project from Moldova. European partners of Moldova Universities are: Scientiﬁc Library of Riga Technical University, Lethonia, University Library of Debrecen, Hungary, Library of Medicine University of Cluj, Romania, the National Council of Student Organization and the Ministry of Education in Moldova. The project will be implemented over three years and will contribute to the diversiﬁcation and modernization of information services for higher education quality.